A Critical Analysis of Stakeholder Perspectives of the Influence of Sales Financial Incentives upon Sales Employee Performance: A Study Conducted within a Medium Size Chinese Financial Services Organization - TAO, YUANYUAN (2017)
Financial incentives had been widely used in the sales industry. The aim of this research is to critically analyse the stakeholder perspectives of the influence of sales financial incentives on sales employee performance. There are two objectives: to examine the impact of financial incentives on employee performance and to analyse how financial incentives influence employee performance based on the employee’s perspective. The research took a case study method in a medium sized Chinese financial services organization. The main findings are that both employees and the HR manager agreed financial incentives have effects on employee performance, but different types of financial incentives differently affected employee performance quantity, performance quality, work effort and retention. Moreover, based on employee perspective, financial incentives could influence employee performance through their expectation, sense of equity and goal-setting, intrinsic and extrinsic motivation and sense of reinforcement. The main conclusions from this research are stakeholders believed financial incentives generally have a positive effect on performance. Specifically, they considered the relationship between the overall financial incentives and performance quantity is positive. Besides, commission may significantly affect employees on maintaining customer relationship, while financial incentives could not affect employee ethical behaviour. Furthermore, the HR manager suggested that basic salary is beneficial for employees who have difficult goals to keep working effort. Both commission and bonuses had been proved by stakeholders, they had positive effects on employee work effort. In case study, financial incentives had less of an impact on employees who did not want to stay in the sales industry. Stakeholders believed Commission and bonuses had a great influence on employee retention. Several recommendations from the case study were offered in these studies for organizations. Organizations can set extra-rewards, then the extra-rewards can have a set ceiling to avoid a goal ceiling problem. High basic salaries could increase the acceptance of difficult goals, this may help employees to maintain and increase performance. Moreover, based on the limitations of the research, some useful recommendations were provided to scholars who are willing to research this area in the future.